Inositol trisphosphate receptor in higher plants: is it real? - Krinke, Ondrej; Novotná, Zuzana; Valentová, Olga; Martinec, Jan (Journal of experimental botany, 2007)
The receptor for D-myo-inositol 1,4,5-trisphosphate (InsP3-R) has been well documented in animal cells. It constitutes an important component of the intracellular calcium signalling system. Today the corresponding genes in many species have been sequenced and the antibodies against some of the InsP3-Rs are available. In contrast, very little is known about its plant counterpart. Only a few published works have dealt directly with this topic. This review summarizes the available relevant data and determines some properties of putative plant receptor(s) including the in silico search for its gene in plant genomes, in vivo evidence, its electrophysiology, the parameters of InsP3-induced calcium release and InsP3 binding, immunological cross-reactivity, and subcellular localization. Future progress in this area seems to be inevitable as, despite the efforts, its gene in plants has not been identified yet.
Keywords: signální transdukce; Genome, Plant; Vacuoles; inositol-1,4,5-trisfosfát - receptory; Inositol 1,4,5-Trisphosphate Receptors; výpočetní biologie; zkřížené reakce; vápník; genom rostlinný; Signal Transduction; Cross Reactions; rostlinné proteiny; Models, Biological; Calcium; intracelulární membrány; zvířata; Plant Proteins; biologické modely; vakuoly; Intracellular Membranes; Computational Biology; Animals